Comparative assessment of the sealing capabilities of Biodentine, Mineral Trioxide Aggregates and Glass Ionomer Cement for the repair of furcal perforations in deciduous molar teeth: An In Vitro Study - Dr. Shemna M K ,Dr.Amith Adhyanthaya , Dr.Marium Raheema ,Dr Vidhya Vijayan , Dr Hrishida P , Dr Laya Vijayaraj, Dr Nileena Balan , Dr Krishna N S , Dr Hanna Kizhakayil Hafiz (South Eastern European Journal of Public Health, 2025)
Aim: This study aimed to investigate the sealing ability of biodentine, glass ionomer cement (GIC), and mineral trioxide aggregate (MTA) in furcal perforations in deciduous molar teeth. Methods: Sixty primary mandibular molars were collected, cleaned, and then divided into three groups of twenty. Artificial furcal perforation were created and repaired using GIC, MTA, or Biodentine. 2% methylene blue was used for 48 hours to test each sample's ability to absorb the dye. To measure the amount of dye leakage, the teeth were dissolved in nitric acid and the supernatant was analyzed using a UV-visible spectrophotometer. Results: The mean absorbance values for biodentine were 0.157 ± 0.01; for GIC, they were 0.406 ± 0.01; and for MTA, they were 0.205 ± 0.01. The statistical analysis using One-way ANOVA and Tukey HSD tests revealed significant differences (p < 0.05) between the groups. The group with the least amount of dye leakage was Biodentine, followed by MTA and GIC. Conclusion: Biodentine exhibited superior sealing ability compared to MTA and GIC in the repair of molar furcal perforations. This suggests that it might be beneficial for clinical applications in pediatric dentistry.